'OK this is hard': Doing emotions in social justice dialogue. (March 2013) - Kuby, Candace R.
In this article, I explore emotions in relation to social justice dialogue and share vignettes to illustrate how emotions are embodied, situated and fissured, drawing upon narrative, critical sociocultural and rhizomatic theories. Data comes from a practitioner inquiry while teaching 5- and 6-year-olds in a summer enrichment program in a relatively affluent, suburban community in the southern USA. The article draws upon Micciche's notion of doing emotions, a view that sees emotion as a verb, something we do in relationship to one another. Analysis focuses on moments of emotional collisions that prompted dialogic conversations about social injustices. I initially thought emotional collisions were off task, but upon closer analysis realize these moments were the richest discussions. Situating teaching from a critical literacy stance, the data demonstrates how children are curious to explore injustices. It is beneficial for educators to embrace the emotional collisions as productive sites of social justice dialogue.